Fine structure of the boundary tissue of the seminiferous tubuli of the vampire bat (Desmodus rotundus, G.; Microchiroptera). - Orsi, A. M.; Vicentini, Carlos Alberto [UNESP]; Dias, S. M.; Moreno, M. H. (My University, 1990)
Structurally the boundary tissue of the vampire bat seminiferous tubuli showed 2 to 5 layers of connective tissue in which elongated contractile cells and lamellar and/or fibrillar collagen were noticed. This boundary tissue forms the seminiferous tubular lamina propria. Its structure was more complex around the seminiferous tubuli near the Capsula testicularis than between the adjacent and contiguous tubuli into the testicular lobuli. The whole ultrastructural organization of the seminiferous lamina propria was described here.
Keywords: animal; bat; connective tissue; electron microscopy; histology; male; seminiferous tubule; testis; ultrastructure; Animal; Chiroptera; Connective Tissue; Male; Microscopy, Electron; Seminiferous Tubules; Support, Non-U.S. Gov't; Testis